Sorting the facts from the lots: Contribution of artisanal and small-scale mining (galamsey) to rural livelihood configurations in sub-Saharan Africa - Baddianaah, Issah; Abdulai, Ibrahim Abu; Dordaa, Felix (Journal of Degraded and Mining Lands Management, 2023)
In recent times, what is common in the scientific literature is findings showcasing the environmental and social menaces associated with artisanal and small-scale mining (ASM)–low-tech, low capital investment, and labor-intensive mineral extraction and processing. However, a better understanding of how ASM shapes livelihood and rural economies may present nuances as to how its negative ramifications can be addressed. As a result, this paper examines how galamsey engenders livelihoods and the transformation of rural economies in Ghana. We produced a nuanced counter-debate to the widely held view that galamsey is evil and a menace to national development by sourcing data from 236 operators using a questionnaire and key informant interviews with 11 relevant stakeholders in north-western Ghana. Findings show that galamsey is a source of employment, income, and accumulation of assets such as houses, motorbikes, cars, and filling stations, which together make the local economy thrive, thereby fostering a local economic boom. However, there is limited collaboration between regulatory agencies and local stakeholders in implementing sustainable mining policies in Ghana. To address this problem, the government should engage local community actors such as the chiefs and landlords, assembly members, and the lead miners on possible steps to streamline and effectively monitor galamsey operations as opposed to military clamp downs.